Contemporary challenges of agricultural law: among globalisation, regionalisation and locality (introductory considerations) - Budzinowski, Roman (Przegląd Prawa Rolnego, 2018)
The purpose of the reflection is to outline certain topical problems and to provide a framework for discussion. The conclusion that can be subsequently drawn is that among other things, the world (global) challenges facing agriculture and food economy must always be taken into account. In meeting today’s challenges, one cannot ignore the process of globalisation, but reference to locality ought to be made at the same time. The teaching of agricultural law should not only be of local nature, but should also address issues relevant to EU law (regional aspect) or see it in a wider international perspective (global aspect). The research must not be limited to the domestic law of a given country, but must also take into account international agricultural law and EU agricultural law (if viewed from the Polish perspective) as well as the interdependencies and tensions between the phenomena of globalisation, regionalisation and the locality. The same is true of the traditional relationship between agriculture and production, and of new relationships, such as agriculture and the market, agriculture and food, agriculture and the environment, and agriculture and rural areas. Each of them is interesting from a cognitive point of view and, what is more, is important in the practice of lawmaking and its application. It is also obvious that the implementation of contemporary challenges of agricultural law requires undertaking and conducting a comparative research. In order to facilitate such research, international cooperation should be widely developed.